Results baseline survey at municipal level in Santander, Colombia - CGIAR Research Program on Climate Change, Agriculture and Food Security (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2017)
Infographic on the main findings of the baseline survey carried out by the project "Tailored agro-climate services and food security information for better decision making in Latin America" (AgroClimas) of the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS ) And the International Center for Tropical Agriculture (CIAT). More information at http://ccafs.cgiar.org/agroclimas